Beyond Streptococcus mutans: Dental Caries Onset Linked to Multiple Species by 16S rRNA Community Analysis - Gross, Erin L. (Public Library of Science, 2012)
Dental caries in very young children may be severe, result in serious infection, and require general anesthesia for treatment. Dental caries results from a shift within the biofilm community specific to the tooth surface, and acidogenic species are responsible for caries. Streptococcus mutans, the most common acid producer in caries, is not always present and occurs as part of a complex microbial community. Understanding the degree to which multiple acidogenic species provide functional redundancy and resilience to caries-associated communities will be important for developing biologic interventions. In addition, microbial community interactions in health and caries pathogenesis are not well understood. The purpose of this study was to investigate bacterial community profiles associated with the onset of caries in the primary dentition. In a combination cross-sectional and longitudinal design, bacterial community profiles at progressive stages of caries and over time were examined and compared to those of health. 16S rRNA gene sequencing was used for bacterial community analysis. Streptococcus mutans was the dominant species in many, but not all, subjects with caries. Elevated levels of S. salivarius, S. sobrinus, and S. parasanguinis were also associated with caries, especially in subjects with no or low levels of S. mutans, suggesting these species are alternative pathogens, and that multiple species may need to be targeted for interventions. Veillonella, which metabolizes lactate, was associated with caries and was highly correlated with total acid producing species. Among children without previous history of caries, Veillonella, but not S. mutans or other acid-producing species, predicted future caries. Bacterial community diversity was reduced in caries as compared to health, as many species appeared to occur at lower levels or be lost as caries advanced, including the Streptococcus mitis group, Neisseria, and Streptococcus sanguinis. This may have implications for bacterial community resilience and the restoration of oral health.